Genes related to osmoregulation and antioxidation play important roles in the response of Trollius chinensis seedlings to saline-alkali stress - Hou, Rongmiao; Yang, Lizhi; Wuyun, Tana; Chen, Shiyao; Zhang, Lu (Frontiers in Plant Science, 2023)
Saline-alkali stress is one of the main abiotic stress factors affecting plant growth and development. Trollius chinensis is a perennial herbal medicinal plant with high values for garden application. However, its response and tolerance to saline-alkali stress is unclear. In this study, we mixed four salts (NaCl: Na2SO4: NaHCO3: Na2CO3) with a concentration ratio of 1:9:9:1, and applied low (40 and 80 mM) and high (120 and 160 mM) saline-alkali stress to analyze osmotic regulation substances, antioxidant systems and the gene expression of T. chinensis. Along with higher saline-alkali stress, the leaf relative water content (RWC) started to decrease only from high stress, while the malondialdehyde (MDA) content in leaves decreased continuously, and the contents of proline (Pro), soluble sugar (SS) and soluble protein (SP) increased compared with control. The activities of antioxidant enzymes and the contents of non-enzymatic antioxidants were increased positively with the accumulation of superoxide anion (O2-·) and hydrogen peroxide (H2O2). For instance, the ascorbic acid-glutathione (AsA-GSH) cycle was enhanced in T. chinensis seedling leaves subject to saline-alkali stress. Principal Component Analysis (PCA) indicates that MDA, Pro, SS, SP, H2O2, O2-·, and GSH are important indexes to evaluate the response and tolerance of T. chinensis to saline-alkali stress. Through RNA-Seq, a total of 474 differentially expressed genes (DEGs) were found in plant under low saline-alkaline stress (40 mM, MSA1) vs. control. Among them, 364 genes were up-regulated and 110 genes were down-regulated. DEGs were extensively enriched in carbohydrate transport, transferase activity, zeatin biosynthesis, ABC transporters, and spliceosome. The transcription factor family MYB, BZIP, WRKY, and NAC were related to its saline-alkali tolerance. In addition, some DEGs encode key enzymes in the processes of osmoregulation and antioxidation, including betaine aldehyde dehydrogenase (BADH), inositol monophosphatase (IMP), chloroperoxidase (CPO), thioredoxin (Trx), and germin-like protein (GLPs) were found. Overall, these findings provide new insights into the physiological changes and molecular mechanism of T. chinensis to saline-alkali stress and lay a foundation for the application of T. chinensis in saline-alkali environment.